The Animal Trade : Evolution, Ethics and Implications. - Phillips, Clive (CAB International, 2016)
The trade in live and dead animals and animal parts is a significant aspect of the global economy, but economic considerations are at odds with animal welfare. This book discusses the background to modern international trade, welfare, and the environmental, economic and cultural issues for farm, zoo and sport animals as well as the pet industry.